2016
DOI: 10.24953/turkjped.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in defense mechanisms, ways of coping with stress and sense of identity in adolescent suicide attempts

Abstract: The main aim of this study was to investigate the gender differences in defense mechanisms, ways of coping with stress and identity formation in relation to adolescent suicidal behavior. This study involved 64 adolescents between 12-17 years of age, who were admitted to the emergency service with a suicide attempt. They were evaluated with a semi-structured clinical interview (K-SADS), Ways of Coping Inventory (WCI), Defense Mechanisms Inventory (DMI) and Sense of Identity Assessment Form (SIAF). 60.9% (n = 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…The association between NTR1 gene polymorphisms and defenses was thus a sex-specific result. In fact, several previous studies have demonstrated significant differences in defenses between the two genders ( 56 58 ), and in agreement, we found significant differences in 10 particular defense styles between male and female subjects in the present study. Moreover, the important effect of the interaction between gender and gene polymorphisms has already been demonstrated on individual differences in personality traits ( 59 61 ).…”
Section: Discussionsupporting
confidence: 93%
“…The association between NTR1 gene polymorphisms and defenses was thus a sex-specific result. In fact, several previous studies have demonstrated significant differences in defenses between the two genders ( 56 58 ), and in agreement, we found significant differences in 10 particular defense styles between male and female subjects in the present study. Moreover, the important effect of the interaction between gender and gene polymorphisms has already been demonstrated on individual differences in personality traits ( 59 61 ).…”
Section: Discussionsupporting
confidence: 93%
“…Males generally show aggressive (externalizing) behaviors during personal problems compared to females who often show auto-aggressive (internalizing) symptomatology. So self-poisoning is the main manner of intoxication in females; whereas drug abuse and addiction are more common in males (Foto-Özdemir et al, 2016). Moreover, women with encountered substance abuse problems mostly show unique barriers to seeking medical help owing to greater stigma, limited access to insurance coverage for addiction treatment and less family support for seeking medical advice (Alvanzo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for inclusion were as follow: 13 years of age or older, fluent in Italian, IQ > 70, no organic causes for presentation, and no known psychotic episodes. A strictly matched control group was introduced with the matching criteria of gender, age, and years of education, because these variables can influence defensive functioning (Cramer, 2009 ; Di Giuseppe, Gennaro, Lingiardi, & Perry, 2019b ; Foto-Özdemir, Akdemir & Çuhadaroglu-Çetin, 2016 ; Whitty, 2003 ). Twenty-six non-UHR patients were recruited from the same clinical centers.…”
Section: Methodsmentioning
confidence: 99%